2020
DOI: 10.1111/1754-9485.13098
|View full text |Cite
|
Sign up to set email alerts
|

Chest computed tomography (CT) features in children with reverse transcription‐polymerase chain reaction (RT‐PCR)‐confirmed COVID‐19: A systematic review

Abstract: To describe the chest CT features reported in children with confirmed COVID-19 infection, published in English literature. A systematic review was completed on PubMed, Embase and Scopus databases on the 1st of June 2020 using the PICO strategy. The NIH Quality Assessment Tool was used to assess the quality of the selected articles. The systematic review was evaluated by Case Series Studies and the Preferred Reporting Items for a Systematic Review and Meta-analysis of Diagnostic Test Accuracy Studies (PRISMA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Although the risk of severe illness is significantly lower than in adults, critical cases have been observed in the pediatric population, particularly in patients with underlying medical conditions[ 160 , 169 ]. The multisystem inflammatory syndrome in children (MIS-C) is a worrisome late complication that presents with multiorgan damage in children previously exposed to COVID-19.…”
Section: Pediatric Manifestationsmentioning
confidence: 99%
“…Although the risk of severe illness is significantly lower than in adults, critical cases have been observed in the pediatric population, particularly in patients with underlying medical conditions[ 160 , 169 ]. The multisystem inflammatory syndrome in children (MIS-C) is a worrisome late complication that presents with multiorgan damage in children previously exposed to COVID-19.…”
Section: Pediatric Manifestationsmentioning
confidence: 99%
“…CT investigations in pediatric COVID-19 patients are limited but consistently show that bilateral involvement occur more often than unilateral involvement and ground-glass opacity is the most common CT abnormalities [ 24 ]. In this study, the rate of bilateral patchy shadowing was also higher than the rate of unilateral patchy shadowing but only 19% of our COVID-19 cases showed ground-glass opacity, possibly due to the fact that CT investigation was performed at the very early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary involvement in CT scan described by Simoni et al in a systematic review, which brought together 166 children, showed mostly bilateral infiltration, between 57 and 75%, and a peripheral distribution between 12.5 and 51.7% (24). The presence of GGO was the most common finding in children with pulmonary involvement, followed by the combination of GGO and consolidation according to different series (24,25). Predominance of lower lobes and upper lobes has been described according to different series suggesting that in children there is not a clear pattern of pulmonary involvement location.…”
Section: Clinical Manifestationsmentioning
confidence: 96%
“…The chest X ray in children was abnormal up to 49.1% even some of them being asymptomatic (23). Pulmonary involvement in CT scan described by Simoni et al in a systematic review, which brought together 166 children, showed mostly bilateral infiltration, between 57 and 75%, and a peripheral distribution between 12.5 and 51.7% (24). The presence of GGO was the most common finding in children with pulmonary involvement, followed by the combination of GGO and consolidation according to different series (24,25).…”
Section: Clinical Manifestationsmentioning
confidence: 97%